2020
DOI: 10.1021/acs.organomet.0c00090
|View full text |Cite
|
Sign up to set email alerts
|

To Bind or Not to Bind: Mechanistic Insights into C–CO2 Bond Formation with Late Transition Metals

Abstract: In transition metal-mediated carboxylation reactions, CO2 inserts into a metal–nucleophile bond. At the carboxylation transition state (TS), CO2 may interact with the metal (inner-sphere path) or may insert without being activated by the metal (outer-sphere path). Currently, there is no consensus as to which path prevails. In order to establish general predictions for the insertion of CO2 into metal–carbon bonds, we computationally analyze a series of experimentally reported Cu, Rh, and Pd complexes. Our focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…19 Given the rapid rate of insertion into R PBP-ligated complexes, we were able to complete a rare kinetic study on CO 2 insertion into a metal alkyl complex. Our results demonstrate that the solvent parameter that is best for predicting the rate of CO 2 insertion is the Dimroth-Reichardt E T (30) parameter. This is analogous to what we have observed for transition metal hydrides, 5b but the dependence of the insertion rate on the solvent is signicantly less pronounced in the case of the metal alkyl complex.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…19 Given the rapid rate of insertion into R PBP-ligated complexes, we were able to complete a rare kinetic study on CO 2 insertion into a metal alkyl complex. Our results demonstrate that the solvent parameter that is best for predicting the rate of CO 2 insertion is the Dimroth-Reichardt E T (30) parameter. This is analogous to what we have observed for transition metal hydrides, 5b but the dependence of the insertion rate on the solvent is signicantly less pronounced in the case of the metal alkyl complex.…”
Section: Discussionmentioning
confidence: 74%
“…Similar ligand effects were previously observed for NHC-Cu complexes. 30 The t Bu PCP-supported complex, ( t Bu PCP)Pd(CH 3 ), also shows a preference for the S E 2 pathway, with a computed barrier of 24.2 kcal mol À1 (TS_Out, Fig. S48 3).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, it was shown that benzylic substrates display an unusual η 6 ‐coordination mode, with the nucleophilic carbon positioned up to 3.6 Å away from rhodium [5] . The same substrate binding mode and preference for an outer sphere CO 2 insertion were found computationally for the chiral Rh‐( S )‐SEGPHOS catalyst [6] . This raises the question how the enantioselectivity is controlled in systems where CO 2 is not constrained through interactions with the metal.…”
Section: Introductionmentioning
confidence: 68%
“…[5] The same substrate binding mode and preference for an outer sphere CO 2 insertion were found computationally for the chiral Rh-(S)-SEGPHOS catalyst. [6] This raises the question how the enantioselectivity is controlled in systems where CO 2 is not constrained through interactions with the metal. Although CO 2 preferably is positioned in the outer sphere, it may still be affected by repulsive and attractive nonbonding interactions with the ligand.…”
Section: Introductionmentioning
confidence: 99%